Circadian pattern of motor activity in adults with attention-deficit/hyperactivity disorder. (3rd July 2017) - Tonetti, Lorenzo; Conca, Andreas; Giupponi, Giancarlo; Natale, Vincenzo
ABSTRACT: This study aims to describe the 24-hour activity rhythm in adults with attention-deficit/hyperactivity disorder (ADHD). A total of 18 ADHD patients and 37 healthy controls (HCs) wore an actigraph for 7 days. ADHD patients showed higher motor activity than HCs at 4:00, 6:00, 15:00 and 16:00 hour. Within the theoretical framework of the two-process model of sleep regulation, the observed data may be explained by lower homeostatic sleep pressure in ADHD. This could lead to an increase in motor activity in the second half of the night, when sleep need decreases more rapidly, and in the first half of the afternoon, when patients do not experience the typical post-lunch dip.